Sprint interval training in hypoxia stimulates glycolytic enzyme activity - Puype, J.; Van Proeyen, K.; Raymackers, J. M.; Deldicque, L.; Hespel, P. (Medicine & Science in Sports & Exercise, 2013)
Purpose: In this study, we compared the effect of sprint interval training (SIT) in normoxia versus hypoxia on muscle glycolytic and oxidative capacity, monocarboxylate transporter content, and endurance exercise performance. Methods: Healthy male volunteers (18-30 yr) performed 6 wk of SIT on a cycling ergometer (30-s sprints vs 4.5-min rest intervals; 3 d/wk) in either normobaric hypoxia (HYP, FiO2 = 14.4%, n = 10) or normoxia (NOR, FiO2 = 20.9%, n = 9). The control group did not train (CON, n = 10). Training load was increased from four sprints per session in week 1 to nine sprints in week 6. Before and after SIT, subjects performed a maximal incremental exercise test plus a 10-min simulated time trial on a cycle ergometer in both normoxia (MAXnor and TTnor) and hypoxia (MAXhyp and TThyp). A needle biopsy was taken from musculus vastus lateralis at rest 5-6 d after the last exercise session. Results: SIT increased muscle phosphofructokinase activity more in HYP (+59%, P < 0.05) than that in NOR (+17%), whereas citrate synthase activity was similar between groups. Compared with the pretest, power outputs corresponding to 4 mmol blood lactate in HYP during MAXnor (+7%) and MAXhyp (+9%) were slightly increased (P < 0.05), whereas values were constant in NOR. VO2max in MAXnor and TT performance in TTnor and TThyp were increased by ~6%-8% (P < 0.05) in either group. The training elevated monocarboxylate transporter 1 protein content by ?70% (P < 0.05). In CON, all measurements were constant throughout the study. Conclusion: SIT in hypoxia up-regulated muscle phosphofructokinase activity and the anaerobic threshold more than SIT in normoxia but did not enhance endurance exercise performance.